Detection of the dasheen mosaic virus in edible aroids using qPCR - Varela-Benavides, Ingrid (2017)
Edible aroids have great economic importance worldwide since they are a source of calories for low-income people and of earnings for small farmers. The edible aroids malanga and taro are important exportation products for Costa Rica, however, as in other countries the yield of the plantations has decreased and the production costs have risen due to the increased incidence of diseases like dasheen mosaic virus (DsMV). The production of free DsMV plants is an important component of the management strategy of aroids and the fast and reliable detection of the virus is an important part of such strategy. This paper presents a sensitive and fast detection protocol of DsMV, the protocol was used to evaluate edible aroids that going to be used in a genetic improvement program. Primers and hydrolysis probe were designed based on the sequences reported from virus isolations in Nicaragua, their specificity was evaluated, and then in vitro grown plants and symptomatic material from field were evaluated. It was possible to successfully detect the presence of DsMV both in symptomatic plants from the field, as in asymptomatic in vitro plants. This protocol could be used for further research on the management of the pathology and for the evaluation of materials requiring export or import sanitary certification.